Effect of Natural and Industrial Juices on Surface Microhardness of Microhybrid and Nanohybrid Composites - Meshki, Razieh; Hoseini, Hanieh (UI Scholars Hub, 2021)
Numerous studies have been conducted on the effect of various beverages on the mechanical properties of tooth-colored materials, however, little is known about the effects of these materials on composites, particularly newer types such as nanocomposites. Objectives: This study aimed to evaluate the surface microhardness of two types of composites, micro-hybrid (point 4) and nanohybrid (premise), after exposure to natural and industrial juices. Methods: In this experimental study, 90 disc-shaped specimens with a thickness of 2 mm and a diameter of 10 mm were taken from two composites, micro-hybrid Point4 (Kerr) and nanohybrid premise (kerr) (two groups of 45). Then, the specimens of each group were divided into 5 subgroups of 9 and were immersed for 7 days for 6 hours in 5 solutions of industrial orange juice, natural orange juice, industrial pomegranate juice, natural pomegranate juice, and distilled water (control group). Surface microhardness of specimens was measured by Vickers device at baseline, one day and one week after immersing. Data was measured by ANOVA, repeated measure test, and independent t-test. A significant level of α was 0.05. Results: The surface microhardness of two types of composites exposed to beverages was reduced significantly. However, no significant difference was found between natural and industrial juices in none of the composites. Conclusions: Natural and industrial juices can affect the surface microhardness of composites, which varies depending on the type of composite and the type of juice and immersion time.